Polar release of pathogenic old world hantaviruses from renal tubular epithelial cells - Krautkrämer, Ellen; Zeier, Martin (Virology journal, 2012)
Epithelio- and endotheliotropic viruses often exert polarized entry and release that may be responsible for viral spread and dissemination. Hantaviruses, mostly rodent-borne members of the Bunyaviridae family infect epithelial and endothelial cells of different organs leading to organ dysfunction or even failure. Endothelial and renal epithelial cells belong to the target cells of Old World hantavirus. Therefore, we examined the release of hantaviruses in several renal epithelial cell culture models. We used Vero cells that are commonly used in hantavirus studies and primary human renal epithelial cells (HREpC). In addition, we analyzed MDCKII cells, an epithelial cell line of a dog kidney, which represents a widely accepted in vitro model of polarized monolayers for their permissiveness for hantavirus infection.